Electrostatic interaction assisted synthesis of a CdS/BCN heterostructure with enhanced photocatalytic effects. Issue 5 (3rd January 2020) - Zheng, Yapeng; Hou, Xinmei; Li, Qun; Fang, Zhi; Yang, Tao; Liang, Tongxiang; Duan, Xiangmei; Shang, Minghui; Yang, Weiyou
Abstract : CdS/BCN composites form a type-II heterojunction via electrostatic interaction assisted supersaturated recrystallization, which exhibits excellent photocatalytic effects. Abstract : In this manuscript, a novel photocatalyst, CdS/BCN composites with CdS nanoparticles in situ grown on BCN nanosheets (CdS/BCN), was synthesized via a simple electrostatic interaction assisted supersaturated recrystallization method. Benefiting from a unique heterostructure, the CdS/BCN composites exhibited highly efficient and stable photocatalytic activity for degrading RhB and methylene blue under visible-light irradiation, and moreover, a high rate constant of 0.115 min −1 has been obtained for degrading RhB, which was much higher than that of most CdS based photocatalysts (0.089 min −1 ). First-principles calculations revealed that the significantly enhanced photocatalytic activity of the CdS/BCN composite was mainly ascribed to the formed type-II heterojunction and the built-in electric field at the interface between CdS nanoparticles and BCN nanosheets, which promote the transfer of photo-generated electrons between CdS and BCN, and the ˙O2 − radical originating from enriched photo-generated electrons was found to be the dominant species that was responsible for the enhanced photocatalytic performance in degrading organic molecules.